Age, Period, and Cohort Effects on Migration of the Baby Boomers in Australia. Issue 6 (21st May 2015) - Sander, Nikola; Bell, Martin
Abstract: The distinctive migration behaviour of the baby boom generation is commonly attributed to cohort size effects, but evidence to date has been drawn primarily from the US context. This paper focuses on inter‐cohort differences in the intensity and pattern of internal migration in Australia with particular attention to the Australian baby boomer generation as it has moved through the life course. A series of generalised linear models are fitted to migration flows to disentangle the effects of age, period, and birth cohort. The results demonstrate that age exerts the largest effect on migration intensity, with cohort effects playing a secondary role, while the effects of period are more subtle. In contrast of the US, cohort effects are not restricted to the baby boom but show a continuous upwards trend that plateaued briefly as the later baby boomers, born in the early 1960s, entered the labour force during rising unemployment in the 1980s. This divergence is traced to a much smaller demographic bulge created by the baby boom in Australia that was substantially enlarged by overseas migration in the 1960s. The findings underline the context‐specific nature of mobility behaviour. Copyright © 2015 John Wiley & Sons, Ltd.